Assessment of resilience engineering factors based on system properties in a process industry. Issue 1 (February 2016) - Shirali, Gh.; Motamedzade, M.; Mohammadfam, I.; Ebrahimipour, V.; Moghimbeigi, A.
Abstract The complexity of modern sociotechnical systems has resulted in new challenges in the safety areas, making traditional approaches no longer sufficient. Therefore, resilience engineering (RE) is a recognizable alternative to traditional approaches in safety management. Our literature review, however, showed that most studies have focused on a set of certain indicators for assessing RE, and other indicators have been left undeveloped. This study aims to represent a new view for assessing RE factors in a process industry using a wide range of indicators, i.e., buffering capacity, margin, tolerance, cross-scale interactions, learning culture, flexibility, anticipation, attention, and response. Related data were collected using semi-structured interviews with multiple-choice questions from 24 experienced operators and eight managers, analysis of documents, team work, as well as friendly and informal conversations. The data were analyzed based on the principal component analysis approach. The results led to determination of poor indicators and units in the industry. This is the first study in assessing RE factors using new indicators that demonstrate the nature of the risk and its complexity in the sociotechnical systems. It can, therefore, be employed as an appropriate method for assessing RE factors.